2009
DOI: 10.1186/1471-2407-9-119
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastasis development and poor survival associated with carcinoembryonic antigen (CEA) level in advanced non-small cell lung cancer: a prospective analysis

Abstract: BackgroundCentral nervous system is a common site of metastasis in NSCLC and confers worse prognosis and quality of life. The aim of this prospective study was to evaluate the prognostic significance of clinical-pathological factors (CPF), serum CEA levels, and EGFR and HER2 tissue-expression in brain metastasis (BM) and overall survival (OS) in patients with advanced NSCLC.MethodsIn a prospective manner, we studied 293 patients with NSCLC in IIIB-IV clinical stage. They received standard chemotherapy. CEA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
103
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 47 publications
12
103
0
1
Order By: Relevance
“…However, no significant correlations between the overexpression of ErbB receptor family members and clinical pathological parameters, including OS time, were observed (24). By contrast, a prospective study assessing the development of brain metastasis in 293 patients with advanced NSCLC reported that EGFR expression (RR, 1.6; 95% CI, 1.4-1.9; P=0.012) was independently associated with a shorter OS time (25). Similarly, a report from a retrospective cohort of patients with NSCLC that assessed HER2 levels demonstrated a higher objective response rate among patients that overexpressed HER2 and were treated with trastuzumab (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant correlations between the overexpression of ErbB receptor family members and clinical pathological parameters, including OS time, were observed (24). By contrast, a prospective study assessing the development of brain metastasis in 293 patients with advanced NSCLC reported that EGFR expression (RR, 1.6; 95% CI, 1.4-1.9; P=0.012) was independently associated with a shorter OS time (25). Similarly, a report from a retrospective cohort of patients with NSCLC that assessed HER2 levels demonstrated a higher objective response rate among patients that overexpressed HER2 and were treated with trastuzumab (26).…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative values of CEA, even within their normal range (0 -5 ng mL ), are related to worse prognoses [71]. Although serum CEA assays have low sensitivity and specificity for diagnosing lung cancers [72], several studies have reported statistically significant evidence for the use of CEA as a prognostic marker in NSCLC patients, but not for SCLC patients [73][74][75][76][77].…”
Section: Lung Cancer Protein Biomarkers In Serum: Current Statusmentioning
confidence: 99%
“…CEA is an oncofetal protein attached to epithelial cell apical membrane via its C-terminal glycosylphosphatidylinositol anchor, a member of the immunoglobulin superfamily of cell adhesion molecules (17). Usually, CEA is overexpressed in a variety of neoplasms, such as colorectal, breast, bladder, gastric, pancreatic and lung carcinomas (16). CEA is a good monitoring marker for conventional chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It appears more sensitive and more specific than other tumor markers, such as CEA and NSE, and slightly better than squamous cell carcinoma-antigen (SCC) in squamous cell carcinoma (15). CEA is a glycoprotein expressed during early fetal life, and is the product of the CEACAM5-gen (16). CEA is an oncofetal protein attached to epithelial cell apical membrane via its C-terminal glycosylphosphatidylinositol anchor, a member of the immunoglobulin superfamily of cell adhesion molecules (17).…”
Section: Discussionmentioning
confidence: 99%